ترجمة النصوص العلمية إلى اللغة العربية: إشكاليات وتحديات - حنو خديجة (University Of Eloued جامعة الوادي, 2022)
تكتسي الترجمة العلمية أهمية بالغة في عالم الترجمة لما لها من فوائد تعود بها على المجتمع العالمي بأسره، وخاصة في الوقت الراهن حيث تتسارع الاكتشافات العلمية والتطورات التي تمس مختلف مجالات الحياة. وعليه أصبح من الصعب على المترجم وخاصة مترجم النصوص العلمية نقل هذه المعارف من لغة إلى أخرى سيما من اللغات الاجنبية الغربية إلى اللغة العربية. وسنحاول في هذه المداخلة الموسومة " ترجمة النصوص العلمية إلى اللغة العربية: إشكاليات وتحديات" تسليط الضوء على اهم الصعوبات والإشكاليات التي تطرحها ترجمة النصوص العلمية إلى اللغة العربية وكذا التحديات التي يقوم بها المترجم لإيصال المعنى كاملا غير منقوص. Abstract: Scientific translation is extremely important in the world of translation because of its benefits to the entire global community, especially at the present time when scientific discoveries and developments affecting various areas of life are accelerating. Therefore, it became difficult for the translator, especially the translator of scientific texts, to transfer this knowledge from one language to another, especially from Western foreign languages, into Arabic. In this intervention tagged "Translating scientific texts into Arabic: Problems and Challenges", we will try to shed light on the most important difficulties and complexities presented by translating scientific texts into Arabic, as well as the challenges that the translator undertakes to convey the meaning completely and without loss.
مداخلة
Keywords: النص العلمي; الترجمة العلمية; الاستراتيجيات الترجمية; التباين العلمي; scientific text; scientific translation; translation strategies; scientific variation